Depression, Anxiety and Stress among School Going Adolescents during COVID-19 Pandemic in a School in Lalitpur District: Online Survey - Nepal, Manju; Nepal, Parbati; Pokharel, Bandana; Panta, Prem Prasad (Journal of Karnali Academy of Health Sciences, 2020)
Introduction: Coronavirus disease (COVID-19) epidemic is a public health emergency worldwide. It poses a challenge to balance the psychological state of every human being including the children. The objective of this study was to identify the depression, anxiety and stress among school going adolescents during COVID- 19 in a school in Lalitpur District.Methods: An online survey was conducted among 105 adolescents studying in grade 9 and 10 of a conveniently selected school in Lalitpur district. Data was collected using Depression Anxiety and Stress Scale– 21 Items (DASS-21) a valid standard tool using a google form developed by researcher. Data entry and analysis was done using SPSS version 16. A descriptive and inferential statistics were calculated. A chi square test for categorical data and correlation coefficient for continuous data were used to establish the relationship between variables. P value ≤ 0.05 was used for statistical significance.Results: More than half 52.4% were from 16 years. The mean age ± SD of respondent was 14.94±.77 years, 59.o% of respondents were from grade 10. More than half of respondpondents (50.5%) were male. Among the respondents, 12.4% had mild, 19.0% had moderate, 5.7% had severe and 6.7% had extremely severe symptoms of depression. Similarly 13.3% had mild, 14.3% had moderate, 2.9% had severe and 13.3% had extremely severe symptoms of anxiety. Conclusion: The symptoms of anxiety, depression and stress is prevalent among school going adolescents during the COVID-19 pandemic.